1996
DOI: 10.1149/1.1836489
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Modeling of Wet Etching of Aluminum Oxide by Warm Phosphoric Acid

Abstract: Aluminum oxide has been used widely in the microelectronic industry for dielectric films. Etching kinetics of vacuum sputtered aluminum oxide films by warm phosphoric acid is studied. The etch rate is found to be constant when the concentration and temperature of the etchant are fixed and the films being etched come from the same deposition batch. Etch rates obtained at different etchant concentrations show that over the industrial range of interest, the kinetics are first order in the hydrogen ion concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 8 publications
2
25
1
Order By: Relevance
“…Following, a 25 nm-thick Al 2 O 3 gate dielectric layer (dielectric constant: 9.5) was deposited by atomic layer deposition (ALD) at 150 C. Gate contact holes through the Al 2 O 3 were patterned by photolithography and wet chemistry. 26 Subsequently, 10 nm/60 nm of Ti/Au were e-beam evaporated and structured into source/drain (S/D) contacts using a lift-off process. Prior to the semiconductor deposition, the substrate was diced into chips of 1.5 Â 1.5 cm 2 .…”
mentioning
confidence: 99%
“…Following, a 25 nm-thick Al 2 O 3 gate dielectric layer (dielectric constant: 9.5) was deposited by atomic layer deposition (ALD) at 150 C. Gate contact holes through the Al 2 O 3 were patterned by photolithography and wet chemistry. 26 Subsequently, 10 nm/60 nm of Ti/Au were e-beam evaporated and structured into source/drain (S/D) contacts using a lift-off process. Prior to the semiconductor deposition, the substrate was diced into chips of 1.5 Â 1.5 cm 2 .…”
mentioning
confidence: 99%
“…Zhou et al reported that the etching rate of the vacuum-sputtered Al 2 O 3 films by warm phosphoric acid (H 3 PO 4 85%, 50°C) was proportional to H ϩ ion concentration. 8 Kikuyama et al reported a relationship between the etching rate and the HF 2…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Therefore, based on their results, the etching process proceeded by the reactions given in Eqs. 1 and 2 8,9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We patterned and etched the semiconductor by standard photolithography (mask 2) and diluted hydrochloric acid [10] (HCl : H 2 O = 1 : 120). To remove the Al 2 O 3 above the gate contact pads, we used photolithography mask 3 and AL-11 aluminium etchant from Cyantek heated to 50 °C [11]. Due to the limited resistivity of a-IGZO against chemical etchants we deposited the upper metal layer (source and drain contacts, interconnects) using a lift off process.…”
Section: A Tft Fabricationmentioning
confidence: 99%